Children with long-term conditions or disabilities: Why some are not in non-parental child care - Allison Leanage; Rubab Arim (Economic and Social Reports, 2025)
Using data from the 2023 Survey on Early Learning and Child Care Arrangements–Children with Long-Term Conditions or Disabilities, this study aimed to identify potential barriers to participating in child care among children with long-term conditions or disabilities who do not regularly attend non-parental child care.